Detection of Gadolinium (Gd) in Tissues - L. Abraham, Jerrold (Current Rheumatology Reviews, 2010)
Analysis of Gadolinium (Gd) in tissues has become important since the discovery of the relationship of Gd exposure to the development of nephrogenic systemic fibrosis (NSF). Microanalytical methods including Scanning Electron Microscopy with Energy Dispersive X-Ray Spectrometry (SEM/EDS), Secondary Ion Mass Spectrometry (SIMS) or X-Ray microscopy allow imaging and analysis of insoluble Gd deposits in routinely fixed and processed biopsy or autopsy tissues. Soluble chemicals may be detectable in frozen/unfixed tissue samples. In situ, non-destructive SEM/EDS analyses have demonstrated insoluble deposits containing Gd with P, Ca and Na in all cases of NSF examined, if sufficient biopsy is available. The presence of Gd bound to phosphate confirms the release of Gd ion from the chelated contrast agent formulation. Gd deposits tend to be more concentrated in deep subcutaneous fibrotic tissue, thus superficial biopsies may be false negative for Gd. SIMS or X-Ray microscopy can detect Gd at concentrations below the sensitivity of SEM/EDS. Inductively coupled plasma mass spectrometry (ICP-MS), a destructive technique, is optimal for determining gravimetric concentration of Gd in tissues, but cannot determine the molecular form of the Gd nor its spatial distribution. Differing analytical methods provide complementary information on Gd in tissues.
Keywords: secondary ion mass spectroscopy